2021
DOI: 10.51470/plantarchives.2021.v21.no1.087
|View full text |Cite
|
Sign up to set email alerts
|

COMPOSITIONAL CHARACTERISTICS OF RUDRAKSHA (ELAEOCARPUS GANITRUS Roxb.)

Abstract: Rudraksha bead or Elaeocarpus ganitrus (Roxb.) is a reverent plant based therapeutic agent with spiritual and holistic importance in traditional system of medicine since time immemorial. While multifarious pharmacological properties of Rudraksha beads have been reported against a range of chronic disorders, evidences about its compositional characteristics are highly superficial. The present study aims to quantify the biochemical, phytochemicals, functional groups, and elemental characteristics of three, four,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In another study, the effects of rudraksha with three, four, and five Mukhi were observed. The findings showed that the content of C and H increased with the introduction of Mukhi rudraksha 45 . It is noticeable that the origin, type, species, and environment all have an impact on the chemical composition of rudraksha.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In another study, the effects of rudraksha with three, four, and five Mukhi were observed. The findings showed that the content of C and H increased with the introduction of Mukhi rudraksha 45 . It is noticeable that the origin, type, species, and environment all have an impact on the chemical composition of rudraksha.…”
Section: Resultsmentioning
confidence: 94%
“…The findings showed that the content of C and H increased with the introduction of Mukhi rudraksha. 45 It is noticeable that the origin, type, species, and environment all have an impact on the chemical composition of rudraksha. It is noticeable that the origin, type, species, and environment all have an impact on the chemical composition of rudraksha.…”
Section: Properties Of Rudrakshamentioning
confidence: 99%
“…Acetone extract of this fruit contains high levels of total phenolic content (104 mg GAE/g) and flavonoid (155 mg RUE/g). The free radical scavenging efficiency of E. recurvatus bark extract was reported (Kumar et al, 2007;Lakshmiet al, 2016;Vuong et al, 2018;Sharma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%